Expression of fas and fas ligand in prostate carcinoma - Berdjis, Navid; Verbeke, Caroline Sophie; Siegsmund, Michael; Bleyl, Uwe; Grobholz, Rainer (Pathology, research and practice, 1999)
Aims: Fas ligand is a member of the tumor necrosis factor (TNF) family and fas of the TNF receptor family which mediate apoptosis. Fas/fas ligand expression of tumor cells may play a role in tumor progression in some tumors such as melanoma. We evaluated the expression of fas and fas ligand in prostatic carcinoma and correlated with tumor staging and grading.